Advanced composite materials for structural maintenance, repair, and control - Aabid, Abdul; Baig, Muneer; Hrairi, Meftah (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
A newly added Special Issue (SI) of the Materials journal, titled "Advanced Composite Materials for Structural Maintenance, Repair, and Control" focuses on the foundations, characterizations, and applications of several advanced composites. This SI aims to publish reviews and research papers on the most recent scientific and practical studies, including those on product development and the lifecycle analysis of improved advanced composites for engineering applications, particularly aeronautical, mechanical, automotive, material, and structural engineering. In several engineering applications, defects including delamination, notch, and fracture are unavoidable. These damages are mostly brought on by fatigue and accidents. Structural repair, rather than replacing the entire component, is sometimes the only viable option when the damage to the material is not extensive. Since passive repairs utilize composite materials, they offer enhanced stress transfer mechanisms and joint efficiency. Over the last four decades, bonded composite repair methods by means of various composite material patches, such as carbon-fiber-reinforced polymers, boron-epoxy, carbon-epoxy, and glass-epoxy, have been developed to repair damaged structures. Because they can withstand the imposed stresses at a fraction of the weight of metallic alloys, these materials were appealing to those who dealt with the maintenance, repair, and control of damaged structures. Since then, the usage of composite materials has spread throughout the world, from secondary to primary structures of the aerospace industry, automotive industry, and other fields. New advanced composite materials, repair methods, simulation approaches, and optimization techniques are still being continuously developed with the objective to control structural damage, minimize fracture parameters, enhance cost efficiency, decrease energy consumption, and offer advanced solutions for repair methods and the maintenance of damaged structures.